Clinical and molecular studies in fragile X patients with a Prader-Willi-like phenotype. Issue 9 (September 1993) - de Vries, B B; Fryns, J P; Butler, M G; Canziani, F; Wesby-van Swaay, E; van Hemel, J O; Oostra, B A; Halley, D J; Niermeijer, M F
Abstract : A special subphenotype of the fragile X syndrome is reported which is characterised by extreme obesity with a full, round face, small, broad hands/feet, and regional skin hyperpigmentation. It resembles the Prader-Willi syndrome (PWS) and might therefore be named 'Prader-Willi-like'. Unlike the PWS, these PW-like fragile X patients lack the neonatal hypotonia with feeding problems during infancy followed by hyperphagia from toddlerhood. We describe five new fragile X patients and present a clinical update of three previously described patients with the PW-like phenotype. In one family, segregation of either the classical Martin-Bell or the PW-like phenotype was observed and in another family there was repeated transmission of the PW-like phenotype. Previously, one of the patients had been misdiagnosed as having classical PWS, based on clinical findings. Molecular studies of the FMR-1 gene showed the typical full mutations as seen in fragile X syndrome males. Molecular analysis of the 15q11-13 region, which is deleted in the majority of classical PWS patients, did not show any detectable abnormalities. In a group of 26 patients with suspected Prader-Willi syndrome but without detectable molecular abnormalities of chromosome 15, one fragile X patient was found. These clinical and molecular findings illustrate the necessity to perform DNA analysis of the FMR-1 gene in mentally retarded patients presenting with a PW phenotype but without the PWS specific cytogenetic/molecular abnormalities of chromosome 15.